Unisphere under construction
Caption, "The third of the three orbital rings encirling the Unisphere is raised in position. Each ring, symbolizing man's achievements in space, measure 8" in diameter - and is constructed of stainless steel tubing. The outside ring extends more than 15 feet from the globe."